2015
DOI: 10.1007/s12274-015-0760-8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-migratory and increased cytotoxic effects of novel dual drug-loaded complex hybrid micelles in triple negative breast cancer cells

Abstract: A polymer-based nanocarrier was developed for the co-delivery of epigenetic and chemotherapeutic drugs. The sterically stabilized hybrid micelle system uses micelles composed of D-α-tocopheryl polyethylene glycol 1000 succinate (vitamin E TPGS or TPGS) and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[methoxy(polyethylene glycol)-2000] (DSPE-PEG2000). In this study, suberoylanilide hydroxamic acid (SAHA) and paclitaxel were used as model drugs for combination chemotherapy to enhance therapeutic efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Recent studies have shown that TPGS could play a role as an anticancer drug enhancer by inhibiting P-glycoprotein-mediated multidrug resistance in multiple tumor cells. [33][34][35][36][37][38] However, few investigations have involved the combination functions of therapy and diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that TPGS could play a role as an anticancer drug enhancer by inhibiting P-glycoprotein-mediated multidrug resistance in multiple tumor cells. [33][34][35][36][37][38] However, few investigations have involved the combination functions of therapy and diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The drug loading capacity of FMP-CNSs for PTX was 800.4 mg/g (~80.4 wt%), which is much higher than that previously-reported other mesoporous silica-based nanocarriers and hybrid micelles (<30.9 wt%). 26,63, 64 The appearance of the characteristic UV-Vis absorption peak of PTX at around 200 nm (Fig. 3d) confirms the successful loading of PTX molecules in FMP-CNSs.…”
Section: Resultsmentioning
confidence: 52%
“…Chitosan-based micelles or microemulsions were also found to be promising brain-targeting delivery systems due to their high brain biodistribution in in vivo studies For brain-targeted cancer treatment, Agrawal et al [96] developed chitosan micelles that were conjugated with transferrin and d-α-tocopherol PEG 1000 succinate (Figure 7B). This showed several benefits, including increased solubility of chitosan in acidic environments, the enhanced permeation of the NCs due to reversible opening of TJs, and inhibition of the P-gp [97][98][99][100]. The resulting micelles had an average size of 15 nm and an average ZP of −3 mV.…”
Section: Discussionmentioning
confidence: 99%